Second Five Year Plan (1956-61) South Arcot District (Madras State) - Planning Commission (Planning Commission, 1956)
The South Arcot district lies between 11° 5' and 12° 30' of the northern latitude and 78° 37' and 80° of the longitude. The district is on the east coast of the Madras State, with Chingloput and North Arcot districts on the north, the Bay of Bengal on the cast. Tanjoro and Tiruchirappalli districts on the south and Salem and North Arcot districts on t he west. The district is, for the most part, a flat plain, sloping very gently from the west to the sea on the east, and also from t he north to the south except for a strip of high ground running across the district from Pondicherry to Vriddhachalam. The Kalroyan Hills running north to south lie in the western part of Kallakurichi taluk and spread out in Salem district. The Gingko Hills in Gingko taluk run from near Gingko south-westwards for about 14 miles.
Madras State